Batch process modelling and economic evaluation of glucuronidase enzyme production - Kamuri, M Firdaus; Foo, Dominic Chwan Yee; Mel, Maizirwan (OMICS Group, 2012)
β-glucuronidases enzyme is a valued product in the pharmaceutical industry. This work features the modeling and optimization of β-glucuronidases enzyme production from recombinant E. coli using SuperPro Designer v5, a commercial batch process simulator. The study focuses on designing an economically viable β- glucuronidases enzyme production process. In the base case process, an annual production of 956 batches (corresponding to 8,523 kg) of β- glucuronidases enzyme was made. Seven alternatives production schemes were further developed for increased production using batch debottlenecking strategy. The best alternative scheme was reported to achieve a product yield of 100% increment, with an annual production of 1912 batches of β- glucuronidases enzyme. Economic analysis determined that the proposed alternative scheme has an annual revenue of USD 44M, with a 15.24% gross margin and a 29.44% of return on investment. The payback period of this scheme was estimated to be less than four years.